Divergent Thinking Differences Between Dungeons & Dragons Players and Non-Players (Revista Científica UCOM Scientia, 2025)
Divergent Thinking is an individual's ability to propose new solutions and modify approaches, making it a key predictor of creative potential. There is evidence that Dungeons & Dragons influences people's creativity. Therefore, this study aims to identify differences in Divergent Thinking between Dungeons & Dragons players and non-players. The sample included 95 individuals, aged 18 to over 60, residing mostly in Asunción and its surrounding areas. Participants were divided into two groups: Players (50.53%) and Non-Players (49.47%). A statistically significant difference was found in Divergent Thinking scores between Dungeons & Dragons Players and Non-Players (sig.=0.050 > p=0.002), leading to the rejection of the null hypothesis. Thus, concluding that Players exhibit higher levels of Divergent Thinking, suggesting that Dungeons & Dragons, beyond being a leisure activity, may serve as a promising tool for fostering Divergent Thinking.Keywords: Dungeons & Dragons, Divergent Thinking, Creativity.
Keywords: Dungeons & Dragons; Divergent Thinking; Creativity